2014
DOI: 10.1155/2014/620391
|View full text |Cite
|
Sign up to set email alerts
|

BCI Sensor Based Environment Changing System for Immersion of 3D Game

Abstract: We present a methodology about game environment system based on BCI (brain computer interface) for immersion of FPS game play. FPS game is a video game genre centered on gun shooting and projectile weapon-based combat through a first-person perspective; immersion is important factor in this game. FPS game designer makes efforts to raise player's immersion using interface, graphic effect, sound, and so forth. We implemented real-time game environment system using game player's emotional state information from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…They claim that the average accuracies of both models, subject-dependent and subject-independent, were approximately 75.62% and 65.12%, respectively. Cho and Lee [11] presented a methodology for game users which is based on Brain Computer Interface. The game called FPS is a common video game focused on gun shooting and projectile weapon based combat on a single user.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They claim that the average accuracies of both models, subject-dependent and subject-independent, were approximately 75.62% and 65.12%, respectively. Cho and Lee [11] presented a methodology for game users which is based on Brain Computer Interface. The game called FPS is a common video game focused on gun shooting and projectile weapon based combat on a single user.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, EEG data of single frequency band (0.5 to 70 Hz) are coming through secured sensors. It is established through previous studies [9][10][11][12] that the desired results from original frequency are difficult to achieve due to some noise artifacts and existence of other unknown signal patterns. We considered five frequency bands in our research, such as delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-50 Hz), also denoted as , , ,…”
Section: Introductionmentioning
confidence: 99%
“…Sollfrank et al [ 49 ] showed that a realistic visualization in 3D of upper and lower limb movements can amplify motor related potentials better than in 2D visualization during subsequent motor imagery. Cho and Lee [ 50 ] implemented a real-time game environment system using game player's emotional state information from the BCI sensor to raise the degree of immersion in an FPS game. Kondo and colleagues [ 51 ] investigated the effect of static and dynamic visual representations of target movements during BCI neurofeedback training, which revealed that dynamic images showed significant improvement in generating MI-associated ERD compared with static images.…”
Section: Discussionmentioning
confidence: 99%
“…Most of current games based on the BCI interface as game play control have been developed to measure the emotional state of the players such as "Sudden Attack", a firstperson shooter game type, developed in Unity3D gaming engine based on ThinkGear BCI plug-in to communicate with PC and that is able to measure four category of emotional states of the player: the attention/inattention and the meditation/uneasiness according to the beta brainwave level recorded that influence the changing of the sky lightening in gameplay environment due to human biological clock [13]. The game playing screen shot is presented in Fig.…”
Section: Bci Related To Gamesmentioning
confidence: 99%